Moroccan Arabic - Heath, Jeffrey (My University, 2020)
Morocco, even if the disputed Western Sahara is excluded, is rivaled only by Yemen in its variety of Arabic dialects. Latin/Romance sub- and ad-strata have played crucial roles in this, especially 1. when Arabized Berbers first encountered Romans; 2. during the Muslim and Jewish expulsions from Iberia beginning in 1492; and 3. during the colonial and post-colonial periods.
Keywords: Morocco; Arabic; Arabic dialects